(untitled) (El-Wahat Journal for Research and Studies, 2023)
ملخص: هدفت الدراسة إلى التعريف باختبار عسر القراءة الذي أعد في إطار أطروحة دكتوراه في الارطوفونيا ، والتحقق من الخصائص السيكومترية للاختبار ، حيث يتكون الاختبار من اثنا عشر (12) بند ، بندين (2) خاصين بقراءة المقاطع و ثمانية (8) بنود خاصة بقراءة الكلمات وبندين (2) خاصين بقراءة النصوص. طبق الاختبار على عينة من التلاميذ العاديين مكونة من 510 تلميذ ، 170 تلميذ في كل سنة (الثالثة والرابعة و الخامسة ابتدائي) . وقد تم الاعتماد على المنهج الوصفي. وكشفت نتائج الدراسة أن الاختبار يتمتع بدرجة عالية من الصدق وذلك بناء على معاملات الارتباط بين البنود والدرجة الكلية للاختبار التي كانت موجبة ودالة احصائيا . كما وقد حقق الاختبار معاملات ثبات جيدة وذلك باستخدام معامل ألفا كرونباخ. كما أسفرت نتائج تحليل البنود عن عدم استبعاد أي بند وعليه تم الاحتفاظ بكل بنود الاختبار لأن لها القدرة على التمييز فبقي عدد البنود 12 بند . كلمات دالة: القراءة، آليات القراءة، عسر القراءة، اختبار عسر القراءة، الخصائص السيكومترية. Abstract: The study aimed at defining the dyslexia test, which was prepared in the framework of a doctoral dissertation in speech therapy, and verifying the psychometric characteristics of the test. (2) For reading texts. The test was applied to a sample of ordinary students consisting of 510 students, 170 students in each year (the third, fourth and fifth primary). The descriptive approach has been relied upon. The results of the study revealed that the test has a high degree of validity, based on the correlation coefficients between the items and the total score of the test, which were positive and statistically significant. The test also achieved good stability coefficients by using Cronbach’s alpha coefficient. The results of the items analysis also revealed that no item was excluded, and therefore all test items were kept because they have the ability to distinguish, so the number of items remained 12 items. Keywords: Test; dyslexia; psychometric properties; Primary school students.